Karakterisasi Stabilitas Termal Kaolin Tatakan Kalimantan Selatan: Muhammad Saukani, Izzatus Sholehah, Saifullah Arief, Sadang Husein - Muhammad Saukani Muhammad Saukani; Izzatus Sholehah Izzatus Sholehah; Saifullah Arief Saifullah Arief; Sadang Husein Sadang Husein (Jurnal Fisika dan Aplikasinya, 2020)
This research is to characterize thermal stability of Kaolin from Tatakan, South Borneo. This research have been done by discussing the thermal treatment provided for kaolin clay and it used as a geopolymer base material. The FTIR, DSC-TGA, and XRD characterize the prepared kaolin clay. The DSC-TGA analysis shows that predehydroxylation occurred at temperatures of 50-120C. In addition, the dehydroxylation process started at 430-650C. However, the most stable condition is at 700-900C. Calcination temperature at kaolin clay was given at 650, 750, and 850C with dwell time of 1, 3, and 5 hours. After that, the calcination clay had characterized by FTIR and XRD. The FTIR results showed that all thermal treatments of metakaolin have formed. It was marked by the loss of the characteristic peak of kaolin with wavenumbers of 3600, and 1600 cm-1. Thermal treatment at a temperature of 750C with a holding time of 3 hours showed the largest amorphous phase formed, which was characterized by a decrease in the highest percentage of transmittance. The crystalline peak of kaolin XRD data at 750C shows that the peak of the crystalline phase of kaolinite was lost. It indicates that metakaolin has formed. Based on the results, it shows that the optimum thermal temperature that given to the kaolin Tatakan to create reactive metakaolin is 750C for 3 hours.